Purification and Characterization of Silica Rice Husk Ash (Oryza Sative L.) From Kupang Regency - Lede, Mega O. L.; Wogo, Hermania Em; Lulan, Theodore Y. K.; Ledoh, Sherlly M. F. (Universitas Nusa Cendana, 2021)
This research had been done to purify and characterize silica from rice husk ash for two varieties of rice from Kupang Regency. The purification method used is the extraction method with alkaline solution (NaOH) and precipitation with acid solution (H2SO4). The stages in this research were preparation of rice husk ash, purification of silica rice husk ash with NaOH and H2SO4 solutions, and characterization covered: determination of acidity and surface area and determination of composition using X-ray fluorescence spectrophotometer (XRF). The results of the surface acidity test showed that the highest acidity was in Ciherang silica from Tarus, which was 2.288 mmol/g. While the surface area test showed that the largest surface area was Inpari 46 silica from Pariti, which was 184.297 m2/g with an optimum contact time of 50 minutes. The results of characterization using XRF exhibited that the highest silica purity was Ciherang rice variety from Tarus, with initial silica content data, purification with NaOH and H2SO4 were 93.9%; 98.2% and 99.1%. So that the purification process with NaOH and H2SO4 is proven to increase the silica content in the sample.